An analytical technique for failure analysis and reliability assessment of grid daily outage performance in distributed power system - Ogunjuyigbe, Jacob Kehinde; Ashigwuike, Evans Chinemezu; Adeyemi, Kafayat; Ngang, Ngang Bassey; Araoye, Timothy Oluwaseun; Onuh, Isaac Ojochogwu; Adole, Benson Stephen; Okoh, Solomon Bala; Endurance, Iboi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
This paper modeled and analyzed the reliability performance of the 132/33 kV substation in Abuja, Nigeria through the historical data collected from the APO substation using MATLAB 2021b. The probability distribution model was applied to determine the daily feeder’s outage using Reliability, availability, mean time to repair (MTR), Failure rate, distribution indices, and mean time between failures (MTBF). Due to the application of smart energy meters, the use of prepaid energy meters has helped to regulate energy demand, reduce network overloading especially during peak hours, and minimize the cost of energy consumed. There are more forced failures in the distribution system due to the switchgear and Transformer failures. There are more forced failures in the distribution system since 2013, which caused a reduction in the number of interruptions even with an increase in several customers linked to the transmission network. The result shows that the system was most available in the year 2015 with an average service availability index (ASAI) value of 98.9971%. The system was least available in year 2011 with an ASAI value of 98.6558%. The paper recommended that there should be interconnections between different feeders through proper configuration of switches or reclosers, to reduce failure occurrence in the network.